Effectiveness and Safety of a Clonidine Adhesive Patch for Children With Tic Disorders: Study in a Real-World Practice - Yang, Chunsong; Kang, BingYao; Yu, Dan; Zhao, Li; Zhang, Lingli (Frontiers in Neurology, 2020)
Background: Real-world evidence includes data from retrospective/prospective observational studies and observational registries, and provides insights beyond those addressed by randomized controlled trials. This study aimed to evaluate the effectiveness and safety of a clonidine adhesive patch (CAP) for children with tic disorder (TD) in a real-world setting (RWS). Methods: This was an open-label, non-interventional, post-marketing, observational study in a RWS. Children diagnosed with TDs were enrolled from a pediatric neurology clinic in China, and the change in tic symptom severity following 6 weeks pharmacologic treatments was investigated using Yale Global Tic Severity Scale (YGTSS) during visits at weeks 0, 4, 8 and 12. Results: Of 150 patients, 76% (114/150) were male (age range, 3.03–14.24 years; mean, 8.11±2.48 years). Patients were divided into three groups: tiapride (n=94), CAP (n=14) and CAP + tiapride (n=42). The mean YGTSS improved 11.02, 15.14, 11.13 points from baseline to posttreatment for tiapride, CAP and CAP + tiapride, respectively, but variance analysis showed there was no significant difference in YGTSS related to different pharmacologic intervention during subsequent visits at weeks 4, 8 and 12. Repeated measure analysis showed there was no significant difference between different medication types for reducing the YGTSS score (F = 0.553, P = 0.576). No serious adverse events (AEs) occurred, and there was no significant difference in the prevalence of AEs between the three groups. Conclusion: The CAP is effective and safe for TD management in a RWS, because of the limitation of sample size and the period of follow up, observational studies with longer-term outcomes and larger sample size are needed.